Cultivars and variety identification and their genetic relationships by randomly amplified polymorphic DNA (RAPD) markers in roselle (Hibiscus sabdariffa L.) - Mohd Yusof, Maszlin; Mohd Saud, Halimi (2009)
Studies were undertaken for identification and determination of genetic variation within three species of Hibiscus through random amplified polymorphic DNA (RAPD) markers using 46 random decamer oligonucleotide primers. They are Hibiscus sabdariffa L., Hibiscus rosasinensis and Hibiscus schizopetalus. A total of 170 fragments were produced by 19 primers of which 88.24 % bands were polymorphic. Genetic diversity was evaluated on the basis of presence and absence of bands. Dendrogram was constructed using the unweighted pair group method with arithmetic average (UPGMA). The cluster analysis indicated that the genotypes developed from the same variety or cultivars clustered very closely in one group. This indicated that relationship between Hibiscus sabdariffa L. and other ornamental Hibiscus species were more divergent. This information is very important for future work in breeding of roselle and provides a major input into conservation biology.